Household catastrophic health expenditure: evidence from Georgia and its policy implications - Zoidze Akaki; Gotsadze George; Rukhadze Natia (BMC, 2009)
Abstract Background To quantify extent of catastrophic household health expenditures, determine factors influencing it and estimate Fairness in Financial Contribution (FFC) index in Georgia to establish the baseline for expected reforms and contribute to the design and fine-tuning of the major reforms in health care financing initiated by the government mid-2007. Methods The research is based on the nationally representative Health Care Utilization and Expenditure survey conducted during May-June 2007, prior to preparing for new phase of implementation for the health care financing reforms. Households' catastrophic health expenditures were estimated according to the methodology proposed by WHO - Ke Xu <abbrgrp>1</abbrgrp>. A logistic regression (logit) model was used to predict probability of catastrophic health expenditure occurrence. Results In Georgia between 2000 and 2007 access to care for poor has improved slightly and the share of households facing catastrophic health expenditures have seemingly increased from 2.8% in 1999 to 11.7% in 2007. However, this variance may be associated with the methodological differences of the respective surveys from which the analysis were derived. The high level of the catastrophic health expenditure may be associated with the low share of prepayment in national health expenditure, adequate availability of services and a high level of poverty in the country. Major factors determining the financial catastrophe related to ill health were hospitalization, household members with chronic illness and poverty status of the household. The FFC for Georgia appears to have improved since 2004. Conclusion Reducing the prevalence of catastrophic health expenditure is a policy objective of the government, which can be achieved by focusing on increased financial protection offered to poor and expanding government financed benefits for poor and chronically ill by including and expanding inpatient coverage and adding drug benefits. This policy recommendation may also be relevant for other Low and Middle Income countries with similar levels of out of pocket payments and catastrophic health expenditures.